Dammarane Sapogenins Improving Simulated Weightlessness-Induced Depressive-Like Behaviors and Cognitive Dysfunction in Rats - Wang, Qiong; Dong, Li; Wang, Mengdi; Chen, Shanguang; Li, Shanshan; Chen, Yongbing; He, Wenlu; Zhang, Hong; Zhang, Yongliang; Pires Dias, Alberto Carlos; Yang, Sijin; Liu, Xinmin (Frontiers in Psychiatry, 2021)
Background: Our studies demonstrated that the space environment has an impact on the brain function of astronauts. Numerous ground-based microgravity and social isolation showed that the space environment can induce brain function damages in humans and animals. Dammarane sapogenins (DS), an active fraction from oriental ginseng, possesses neuropsychic protective effects and has been shown to improve depression and memory. This study aimed to explore the effects and mechanisms of DS in attenuating depressive-like behaviors and cognitive deficiency induced by simulated weightlessness and isolation [hindlimb suspension and isolation (HLSI)] in rats. Methods: Male rats were orally administered with two different doses of DS (37.5, 75 mg/kg) for 14 days, and huperzine-A (1 mg/kg) served as positive control. Rats were subjected to HLSI for 14 days except the control group during drug administration. The depressive-like behaviors were then evaluated by the open-field test, the novel object recognition test, and the forced swimming test. The spatial memory and working memory were evaluated by the Morris water maze (MWM) test, and the related mechanism was further explored by analyzing the activity of choline acetyltransferase (ChAT), acetylcholinesterase (AChE), and superoxide dismutase (SOD) in the hippocampus of rats. Results: The results showed that DS treatment significantly reversed the HLSI-induced depressive-like behaviors in the open-field test, the novel object recognition test, and the forced swimming test and improved the HLSI-induced cognitive impairment in the MWM test. Furthermore, after DS treatment, the ChAT and SOD activities of HLSI rats were increased while AChE activity was significantly suppressed. Conclusions: These findings clearly demonstrated that DS might exert a significant neuropsychic protective effect induced by spaceflight environment, driven in part by the modulation of cholinergic system and anti-oxidation in the hippocampus.